The Analysis of the Short-term Capital Movements by Using the VAR Model: The Case of Turkey (The Pakistan Development Review, 2001)
This paper investigates the relations among short-term capital inflows, government deficit, interest rate differentials, real exchange rate and some accounts of the balance of payments in Turkey in 1990s by using the vector autoregression (VAR) technique. The dynamic behaviours of each variable due to random shocks given to short-term foreign liabilities are captured by impulse response functions, and the portion of variance in the prediction for each variable in the system that is attributable to its own innovations and to shocks to other variables in the system is analysed by variance decomposition method. It is found that the policy of high interest-low exchange rate (hot money) is the main reason for the short-term capital inflows in Turkey, and we propose some main controls on capital inflows to limit some of the macroeconomic repercussions of these inflows.